The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/cen.14006
|View full text |Cite
|
Sign up to set email alerts
|

Residual endogenous corticosteroid production in patients with adrenal insufficiency

Abstract: ObjectiveThis study aimed at comparing precursors of endogenous corticosteroid production in patients with primary adrenal insufficiency and in secondary adrenal insufficiency.DesignTwenty patients with primary adrenal insufficiency and matched controls and 19 patients with secondary adrenal insufficiency participated in this ancillary analysis of two different studies.Patients and measurementsPatients with primary adrenal insufficiency were on stable hydrocortisone and fludrocortisone therapy. Patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…17 These studies have recently been extended by 3 different groups using mass spectrometric steroid metabolome assays in a further 249 individuals with established AAD (Table 1). [18][19][20] In summary, these three additional studies have used more sensitive assays to establish beyond doubt that AAD patients are heterogeneous in terms of adrenal function, with around 30% having some low level, residual adrenal steroidogenesis for many years following diagnosis. In the two largest studies around 10% had detectable serum cortisol concentration ≥100 nmol/l and 5% had concentrations ≥150nmol/l.…”
Section: What Is Residual Adrenal Function?mentioning
confidence: 99%
See 4 more Smart Citations
“…17 These studies have recently been extended by 3 different groups using mass spectrometric steroid metabolome assays in a further 249 individuals with established AAD (Table 1). [18][19][20] In summary, these three additional studies have used more sensitive assays to establish beyond doubt that AAD patients are heterogeneous in terms of adrenal function, with around 30% having some low level, residual adrenal steroidogenesis for many years following diagnosis. In the two largest studies around 10% had detectable serum cortisol concentration ≥100 nmol/l and 5% had concentrations ≥150nmol/l.…”
Section: What Is Residual Adrenal Function?mentioning
confidence: 99%
“…All studies found that the glucocorticoid precursor 11deoxycortisol, either in serum or urine, correlated strongly with serum cortisol concentration, making it a potentially useful marker of residual adrenal steroidogenesis that might be ascertained in patients who continued to take their regular medications. [18][19][20] Interestingly, six of 84 participants with residual function had AAD for 20 or more years, 19,20 suggesting that it is a durable state in some patients, although overall residual steroidogenesis was commoner in patients with shorter disease duration. One patient had originally been studied in 2012, 4 years after presentation with AAD when she had a peak stimulated serum cortisol of 184 nmol/L (6.7 ug/dL); repeat measurement in 2016 showed a concentration of 252 nmol/L (9.1 ug/dL).…”
Section: What Is Residual Adrenal Function?mentioning
confidence: 99%
See 3 more Smart Citations